COLLOCATION KNOWLEDGE AND READING ABILITY: A CORRELATIONAL STUDY AT 5TH SEMESTER STUDENTS - Enyla Rama Rani; Risnawati Risnawati (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Collocations are always present in every reading. Reading comprehension followed by collocation mastery. The objective of this research is (1) to investigate the students’ lexical mastery of collocation (2) to investigate the students’ reading comprehension achievement (3) to investigate significant correlation between students’ lexical mastery of collocation and their reading comprehension achievement in English Department at 5th Semester of UIN Fatmawati Sukarno Bengkulu. Correlational study was applied as a method. There were 30 students taken as the sample of this research. The data were collected by using lexical collocation and reading comprehension achievement test. In analyzing the data, this research used Pearson Product Moment Correlation and SPSS 25. The result showed that (1) the score of lexical collocation test was 93.3 % with category is poor (2) the score of reading comprehension test was 66.7% with category is very poor. Finally, it can be conclude that the correlation between students’ lexical mastery of collocation and their reading comprehension is fair. It means alternative (H1) was accepted while null (H0) was rejected. Moreover, since low lexical collocation mastery can affect low reading comprehension achievement, it is hoped that the knowledge and ability of students on lexical collocation can be improved better by the teacher.